2020
DOI: 10.2478/aup-2020-0009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Community Involvement in Participatory Process – Lessons Learned in the Baltic Sea Region

Abstract: For exploring and discovering the main knowledge, experience and practices, four main issues were analyzed: what were the goals of the involved participants regarding the community involvement in the spatial and community planning; what methods were used to extend the involvement of community members; what problems and obstacles did the project participants face, and what were the main lessons learned. This study provides reflections (analysis, comparison and evaluation) on community involvement in participato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In reconstruction efforts conducted in a paternalistic, philanthropic way or with a community-based approach as a means of attaining long-term sustainability after a natural catastrophe, community plays important role in planning and development process (Geipele & Auziņš, 2015;Geipele et al, 2021;Puķīte & Geipele, 2017). The Centre for Research on the Epidemiology of Disasters (CRED) in Brussels, Belgium, reports that India is the most impacted nation in South Asia.…”
Section: Post-disaster Housing Reconstructionmentioning
confidence: 99%
“…In reconstruction efforts conducted in a paternalistic, philanthropic way or with a community-based approach as a means of attaining long-term sustainability after a natural catastrophe, community plays important role in planning and development process (Geipele & Auziņš, 2015;Geipele et al, 2021;Puķīte & Geipele, 2017). The Centre for Research on the Epidemiology of Disasters (CRED) in Brussels, Belgium, reports that India is the most impacted nation in South Asia.…”
Section: Post-disaster Housing Reconstructionmentioning
confidence: 99%
“…In fact, responsible tourism emphasizes behavioral factors, such as showing respect towards people and the planet and establishing collaboration between stakeholders. Geipele et al (2021) suggested that there are many forms of communication with community members other than just classical methods like workshops, meetings, and trainings. While classical methods are more formal, non-classical methods allow communication to take place anywhere beyond just a meeting room and offer better control over the decisions and results achieved.…”
Section: Community Orientationmentioning
confidence: 99%
“…Recently, Geipele, et al [ 18 ] highlighted several specific spatial planning problems of coastal communities in the Baltic Sea region by evaluating community involvement in participatory processes: (a) lack of communication, regardless of country and region; (b) the weak involvement of different social groups; (c) insufficient coastal and environmental management; (d) excessive regulatory enactments; and (e) summer-year-round population conflict. These problems must be taken into account, but have not been analysed in this study.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In this section, the authors have used information and conclusions from parallel and previous research conducted by individual study authors on the phases [ 5 ] and methods [ 18 ] of public involvement in spatial development.…”
Section: Comparison and Evaluation Of Formal And Informal Spatial Planning Process In Latvia Estonia åLand Islands Of Finland And Swedenmentioning
confidence: 99%